Incidencia de la participación ciudadana, periodo fiscal 2021 en la elaboración del presupuesto participativo del GAD Parroquial Rural de Canuto - Muñoz Intriago, Xeomara Estefanía (2023)
Citizen participation is a fundamental component of democracy and allows citizens to get involved in public affairs and influence decision-making. In the research carried out in the Rural Parish GAD in Canuto, we sought to analyze the incidence of citizen participation in the preparation of the participatory budget during the 2021 fiscal period. The research used a combination of bibliographic, field and descriptive methodology. In addition, inductive, deductive and analytical methods were applied to analyze the collected data. This provided a normative context for the study and made it possible to obtain both qualitative (through the interview) and quantitative (through the citizen survey) information. The results obtained revealed that 39% of those surveyed considered that the authorities took their opinions into account for the participatory budget. However, 29% of the population expressed their interest in receiving information about the participatory budget through a web page to be more informed. These results indicate that, although there is some degree of citizen participation, there is still room to improve communication and transparency in the participatory budgeting process. Based on these conclusions, the development of an improvement plan that included strategies to strengthen the relationship between authorities and citizens was proposed. It is important to highlight that this improvement plan was socialized with the help of the authorities of the Rural Parish GAD in Canuto, which demonstrates its commitment to the development of the well-being of the parish.